Private sector corruption: realities, difficulties of comprehension, causes and perspectives: the Lithuanian approach - Pakstaitis, Laurynas (Crime, law and social change, 2019)
The problem of corruption has many significant aspects. With the growth of powers of business and transition of powers from state to private entities problem of private sector corruption becomes more important. While states employ legal and social mechanisms to make an impact on corruption the private sector is usually left with lesser attention. As experience of Lithuania shows even when such attention is pointed towards the private sector and business it sometimes is not adequately judged. If such attention presents traditional institutional approach without proper understanding of the depth of the problem inadequacy and sluggishness prevail. This paper focuses on concepts of corruption in the private sector, the academic ideas, conceptual backings, also presents the difficulties of characterization, analysis of legal acts and shortcomings thereof. The legal tools employed in Lithuania to combat business corruption are analyzed. For the proper understanding of the problem author points out the major reasons behind the private sector corruption, presents the significance of economic motivation as well as the causal spectrum of private sector corruption. The significance of business ethics and self regulation mechanisms and various shortcomings related to them are analyzed.